Worsening ulceration of infantile hemangioma after initiation or escalation of propranolol. Issue 2 (17th February 2022) - Meyer‐Mueller, Cameron; Nicholson, Cynthia; Polcari, Ingrid; Boull, Christina; Maguiness, Sheilagh
Abstract: For infantile hemangiomas (IH) requiring treatment, including those in high‐risk locations or in the setting of ulceration, oral propranolol is first‐line therapy. Here, we present three cases of infantile hemangioma with worsening ulceration following initiation or escalation of oral propranolol at standard doses.